Centrosome amplification and clonal evolution in multiple myeloma: Short review - Kryukova, Elena; Kryukov, Fedor; Hajek, Roman (Critical reviews in oncology/hematology, 2016)
Multiple myeloma (MM) is composed of an array of multiple clones, each potentially associated with different clinical behavior. Previous studies focused on clinical implication of centrosome amplification (CA) in MM show contradictory results. It seems that the role of CA as well as CA formation in MM differ from other malignancies. This has brought about a question about the role of CA positive clone which is--is it going to be a more aggressive clone evolutionally arising under pressure of negative conditions or can CA serve as a marker of cell abnormality and lead to cell death and further elimination of this damaged subpopulation? This current review is devoted to the discussion of the existence of MM subclones with centrosome amplification (CA), its evolutionary behaviour within intraclonal heterogeneity as well as its potential impact on the disease progression and MM treatment.
Keywords: fyziologický stres; Centrosome; Humans; buněčné klony; Disease Progression; Multiple Myeloma; Carcinogenesis; klonální evoluce; Clonal diversification; Centrosome amplification; lidé; proliferace buněk; apoptóza; mnohočetný myelom; Stress, Physiological; Clone Cells; Proliferation; karcinogeneze; Cell Proliferation; progrese nemoci; centrozom; Clonal Evolution; Multiple myeloma; Apoptosis